Berberine Reduces Lipid Accumulation in Obesity via Mediating Transcriptional Function of PPARδ - Shou, Jia-Wen; Shaw, Pang-Chui (International journal of molecular sciences, 2023)
Obesity is defined as a dampness-heat syndrome in traditional Chinese medicine. Coptidis Rhizoma is an herb used to clear heat and eliminate dampness in obesity and its complications. Berberine (BBR), the main active compound in Coptidis Rhizoma, shows anti-obesity effects. Peroxisome proliferator-activated receptors (PPARs) are a group of nuclear receptor proteins that regulate the expression of genes involved in energy metabolism, lipid metabolism, inflammation, and adipogenesis. However, whether PPARs are involved in the anti-obesity effect of BBR remains unclear. As such, the aim of this study was to elucidate the role of PPARs in BBR treatment on obesity and the underlying molecular mechanisms. Our data showed that BBR produced a dose-dependent regulation of the levels of PPARγ and PPARδ but not PPARα. The results of gene silencing and specific antagonist treatment demonstrated that PPARδ is key to the effect of BBR. In 3T3L1 preadipocytes, BBR reduced lipid accumulation; in high-fat-diet (HFD)-induced obese mice, BBR reduced weight gain and white adipose tissue mass and corrected the disturbed biochemical parameters, including lipid levels and inflammatory and oxidative markers. Both the in vitro and in vivo efficacies of BBR were reversed by the presence of a specific antagonist of PPARδ. The results of a mechanistic study revealed that BBR could activate PPARδ in both 3T3L1 cells and HFD mice, as evidenced by the significant upregulation of PPARδ endogenous downstream genes. After activating by BBR, the transcriptional functions of PPARδ were invoked, exhibiting negative regulation of CCAAT/enhancer-binding protein α (Cebpα) and Pparγ promoters and positive mediation of heme oxygenase-1 (Ho-1) promoter. In summary, this is the first report of a novel anti-obesity mechanism of BBR, which was achieved through the PPARδ-dependent reduction in lipid accumulation.